PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN MINAT BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII1 SMPN 1 BANTAN - Anggraini, Rini Dian; Saragih, Sehatta; ', Sudarmono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absract : This research was conducted based on the student’s low interest in math of students class VIII1at SMPN 1 Bantan with percentage 50%. This research was classroom action research. This research aimed to improve students’ interest in math with TSTST cooperative Learning Model. The subjects of this research were students of class VIII1 at SMPN 1 Bantan year 2015/2016. The numbers of students in this research were 20 students consist of 8 male students and 12 are female. The instrument of data collected were observation sheets activities of teachers and students and questionnaire of student’s interest in math. The observation sheets were analysed with qualitative, while the questionnaire were analysed by descriptive quantitative. Based on both analysis showed the improvement of students interest in math before and after the research. The result showed the increasing of students interest for 19% from the previous number before the research was done that is 59% to 70% after the research. Based on the result of the research, we can conclude that the implementation of Cooperative Learning Model type Two Stay Two Stray (TSTS) can improve students’ interest in math of students class VIII1 at SMPN 1 Bantanacademic year 2015/2016.Keywords: Students interest in math, Cooperative Learning Model Type Two Stay Two Stray (TSTS), Classroom Action Research.